Simultaneous determination of paracetamol, caffeine and codeine in tablets and human plasma by micellar liquid chromatography - Belal, Fathalla; Omar, Mahmoud Ahmed; Derayea, Sayed; Zayed, Sahar; Hammad, Mohamed Abdelkhalek; Saleh, Safaa Fathy (European Journal of Chemistry, 2015)
A simple, rapid, sensitive and eco-friendly liquid chromatographic method was developed and validated for the simultaneous determination of paracetamol (PAR), caffeine (CAF) and codeine (COD). The separation was performed on cyano column using a micellar mobile phase consists of 140 mM sodium dodecyl sulfate, 25 mM phosphate buffer and 10% acetonitrile at pH = 3. The analysis was performed at a ﬂow rate of 1 mL/min and a column temperature of 30 °C under direct UV detection at 210 nm. Total analysis time was below 6 min. Baclofen (BCF) was used as an internal standard. The validation was performed according to the ICH guidelines. The proposed method was linear over the ranges of 0.2-100.0, 0.02-12.0 and 0.2-12.0 µg/mL for PAR, CAF and COD, respectively. The limits of detection were 0.031, 0.007 and 0.054 µg/mL and limits of quantification 0.103, 0.02 and 0.164 µg/mL for PAR, CAF and COD, respectively. The results show that the procedure is suitable for the routine analysis of drugs in tablet dosage forms. The method was further extended to the determination of the studied drugs in spiked human plasma with mean percentage recoveries of 99.61±0.530, 99.28±0.523 and 99.52±0.385 for PAR, CAF and COD, respectively.